2020
DOI: 10.3390/ijerph17217803
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Dimensions and Its Association with Risk of Diabetes in Middle and Older Aged Chinese People

Abstract: Background: Diabetes and physical inactivity are prevalent worldwide. Risk of diabetes is known to be related with insufficient physical activity (PA), but associations with the respective dimensions of PA is unclear. Objective: To describe the patterns of physical activity among Chinese middle- and older-aged individuals and figure out their associations with diabetes risk in different dimensions. Methods: Extracting self-reported data from China Health and Retirement Longitudinal Study (CHARLS, 2015), this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The prevalence of hypertension and diabetes mellitus are quite high in China [ 28 , 29 ]. Previous studies found that PA was associated with lower risks of hypertension and diabetes mellitus [ 30 , 31 , 32 ]. Furthermore, older groups and men had higher population-attributable risks of most risk factors of strokes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension and diabetes mellitus are quite high in China [ 28 , 29 ]. Previous studies found that PA was associated with lower risks of hypertension and diabetes mellitus [ 30 , 31 , 32 ]. Furthermore, older groups and men had higher population-attributable risks of most risk factors of strokes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of PA was categorized into five levels: no activity, 10–29, 30–119, 120–239, and ≥240 min/d. Considering that the average of each duration is used in the questionnaire instead of the specific duration ( 16 ), we calculated the total volume of VPA/MPA/LPA in a week by multiplying the frequency and duration of VPA/MPA/LPA. In addition, referring to WHO guidelines ( 17 ), the total amount of VPA was divided into four levels: no activity, 10–74, 75–299, and ≥300 min/w, while the total time per week of MPA/LPA was divided into four levels: no activity, 10–149, 150–299, and ≥300 min/w.…”
Section: Methodsmentioning
confidence: 99%
“…The data collected for this study were from wave 4 of the China Health and Retirement Longitudinal Study (CHARLS). In brief, the CHARLS is a longitudinal study assessing the health, social, and economic status of a nationally representative sample covering 450 villages and 150 counties in 28 provinces in China ( 31 ). The CHARLS collected high-quality data through one-on-one interviews with a structured questionnaire, using multilevel stratification probabilities proportional to sample size to select residents aged 45 years and older from constituting a nationally representative sample.…”
Section: Methodsmentioning
confidence: 99%